2023
DOI: 10.1039/d3gc00913k
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanism of enhanced alcoholysis of biomass carbohydrates to alkyl levulinates over bifunctional catalysts: does it resemble that in water?

Abstract: The catalytic hydrolysis/alcoholysis of biomass carbohydrates into levulinic acid/levulinate esters (alkyl levulinates) as green biofuels and value-added chemicals holds great promise for achieving the goals of sustainable chemistry. Bifunctional catalysts...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…Thus, in this microreview, we summarized the performance of heterogeneous catalysts in the conversion of the biomass-derived molecules into alkyl levulinates and described the design and development of the heterogeneous catalysts that facilitated excellent yields of the target products. We believe that this microreview will furnish subsequent studies with valuable information on the Alkyl levulinates can be synthesized directly from carbohydrates such as cellulose, glucose, and fructose [16,17]. However, this method has frequently given target products in relatively low yields and selectivities due to the formation of multiple products [18].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, in this microreview, we summarized the performance of heterogeneous catalysts in the conversion of the biomass-derived molecules into alkyl levulinates and described the design and development of the heterogeneous catalysts that facilitated excellent yields of the target products. We believe that this microreview will furnish subsequent studies with valuable information on the Alkyl levulinates can be synthesized directly from carbohydrates such as cellulose, glucose, and fructose [16,17]. However, this method has frequently given target products in relatively low yields and selectivities due to the formation of multiple products [18].…”
Section: Introductionmentioning
confidence: 98%
“…The addition of alkyl levulinates to biodiesel can address these drawbacks because of their properties such as low toxicity, high lubricity, flash point stability, and moderate flow properties under low-temperature conditions [3,11,15]. Alkyl levulinates can be synthesized directly from carbohydrates such as cellulose, glucose, and fructose [16,17]. However, this method has frequently given target products in relatively low yields and selectivities due to the formation of multiple products [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that base-mediated enhanced proton transfer through a water bridge causes stabilization of the transition state in the H 2 heterolysis rate-determining reaction step. Ghorbanpour et al showed that in the reaction of decomposition of formic acid, more hydrogen gas is released when sodium formate is used. , Alkyl levulinates (ALs) are biomass-based chemicals with many applications in various fields and can replace chemicals produced from petrochemical pathways. Among the uses of ALs, one can mention their role as a solvent, additive, and precursor in producing gamma-valerolactone (GVL). Ethyl levulinate (EL) is an ester with a fruity odor and can be prepared from levulinic acid (LA) or the reaction between furfuryl alcohol and ethanol. Considering the existence of various sources for EL production, it can be pointed out that this combination is a suitable option for biofuel additives .…”
Section: Introductionmentioning
confidence: 99%